Ferroptosis and multi-organ complications in COVID-19: mechanisms and potential therapies - Li, Qi; Chen, Zeyuan; Zhou, Xiaoshi; Li, Guolin; Zhang, Changji; Yang, Yong (Frontiers in Genetics, 2023)
COVID-19 is an infectious disease caused by SARS-CoV-2, with respiratory symptoms as primary manifestations. It can progress to severe illness, leading to respiratory failure and multiple organ dysfunction. Recovered patients may experience persistent neurological, respiratory, or cardiovascular symptoms. Mitigating the multi-organ complications of COVID-19 has been highlighted as a crucial part of fighting the epidemic. Ferroptosis is a type of cell death linked to altered iron metabolism, glutathione depletion, glutathione peroxidase 4 (GPX4) inactivation, and increased oxidative stress. Cell death can prevent virus replication, but uncontrolled cell death can also harm the body. COVID-19 patients with multi-organ complications often exhibit factors related to ferroptosis, suggesting a possible connection. Ferroptosis inhibitors can resist SARS-CoV-2 infection from damaging vital organs and potentially reduce COVID-19 complications. In this paper, we outline the molecular mechanisms of ferroptosis and, based on this, discuss multi-organ complications in COVID-19, then explore the potential of ferroptosis inhibitors as a supplementary intervention for COVID-19. This paper will provide a reference for the possible treatment of SARS-CoV-2 infected disease to reduce the severity of COVID-19 and its subsequent impact.